ANALISIS RASIO PROFITABILITAS DAN RASIO AKTIVITAS MENJADI DASAR PENILAIAN KINERJA KEUANGAN KSP KARYA MANDIRI - Andres Putranta Sitepu, (Juremi: Jurnal Riset Ekonomi, 2023)
The purpose of this research is to evaluate KSP Karya Mandiri's financial performance from 2020 to 2022, specifically focusing on profitability ratios, and activity ratios, and comparing its performance with industry benchmarks. The research method used is qualitative, utilizing the KSP Karya Mandiri financial statements as the main analysis. Secondary data is used, and data collection techniques include interviews and literature. The results show that KSP Karya Mandiri has performed very well in terms of gross profit margin, outperforming the industry average by an average of 64%. In addition, net profit margins are also impressive, exceeding the industry average by 35%. Return on investment is considered satisfactory, meeting industry standards of an average of 27%. However, when looking at the activity ratio, KSP Karya Mandiri does not manage its assets effectively. Average accounts receivable turnover was significantly lower than the industry standard at only 5 times, and inventory turnover fell below industry expectations at 1 time. On the other hand, total asset turnover is considered adequate, in line with the industry standard average of 1 time. In conclusion, profitability ratios and activity ratios provide valuable insights into a company's financial performance, resource utilization, cost control measures, and sales effectiveness and efficiency.